2017
DOI: 10.18203/2320-1770.ijrcog20175246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anemia on pregnancy outcome: a prospective study at tertiary care hospital

Abstract: Background: Iron deficiency anaemia during pregnancy leads to preterm birth, low birth weight and small-for-gestational age babies and increases incidence of postpartum haemorrhage (PPH) and the reason for the incidence of PPH is higher in India compared with the rest of the world. The objective of this study was to find association between maternal anaemia and neonatal complications and to find long term morbidity and mortality of babies born to anaemic mothers.Methods: It is a prospective study done at Obste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
7
5
0
1
Order By: Relevance
“…Unbooked women were significantly more in group A, similar to other studies [13,7] in which obstetric risks are found to be high [11] . Illiteracy, poverty, lack of awareness of prenatal care and accessibility of health facilities might be the factors that women do not come for availing antenatal services.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Unbooked women were significantly more in group A, similar to other studies [13,7] in which obstetric risks are found to be high [11] . Illiteracy, poverty, lack of awareness of prenatal care and accessibility of health facilities might be the factors that women do not come for availing antenatal services.…”
Section: Discussionsupporting
confidence: 90%
“…All the women were followed up postpartum till discharge. Most of the women in group A had microcytic hypochromic type of anemia (Table 1) similar to other studies [10,11] . Milman has suggested iron deficiency as the commonest cause of anemia [12] .…”
Section: Discussionsupporting
confidence: 88%
“…Women belonging to middle and upper socioeconomic status comprised 36% in group A compared to 60% in group B in our study. Similar observations has been made by Sharma et al and Upadhyay et al 22,24 Lokhare et al, Khatod et al in their study have reported that the severity of anemia decreases as the education level and socioeconomic status increases. 25,26 Anemia in antenatal women is thus inversely related to the literacy status.…”
Section: Discussionsupporting
confidence: 88%
“…These were comparable with the observation of Upadhyay C et al were Preterm deliveries was 20%, IUGR 11.5% and IUD 3% and Awasthi A et al PT (9.5%), IUGR (37.5%) and IUD (8%) and also comparable with Rangnekar et al PT (73%), IUGR (4%) and IUD (16%). 7,12,13 In this study most common cause of anemia is iron deficiency anemia (69.6%) followed by sickle cell anemia (15.4%) as incidence of sickle cell anemia is very high in Chhattisgarh as shown in study of Lagoo J et al (17%). Similarly, Cochrane review 2009 shows that microcytic hypochromic anemia resulting from iron deficiency is the most frequent form of anemia (76%), followed by folate deficiency (20%) and combined iron and folate deficiency (20%).…”
Section: Resultsmentioning
confidence: 57%